2020
DOI: 10.1186/s12889-020-08559-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight development between age 5 and 10 years and its associations with dietary patterns at age 5 in the ABCD cohort

Abstract: Background: Social inequalities in bodyweight start early in life and track into adulthood. Dietary patterns are an important determinant of weight development in children, towards both overweight and underweight. Therefore, we aimed to examine weight development between age 5 and 10 years by ethnicity, SES and thereafter by BMI category at age 5, to explore its association with dietary patterns at age 5. Methods: Participants were 1765 children from the Amsterdam Born Children and their Development (ABCD) coh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In one study, an association with BMI at 7 years was found only among girls [17]. Moreover, studies with the longest follow-up period (up to 5 years) reported either no or mixed associations between various dietary patterns at age 3 or 5 and weight-related outcomes later in childhood [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…In one study, an association with BMI at 7 years was found only among girls [17]. Moreover, studies with the longest follow-up period (up to 5 years) reported either no or mixed associations between various dietary patterns at age 3 or 5 and weight-related outcomes later in childhood [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Healthy eating behaviors characterized by the NQ-P score, such as consuming a variety of foods, limiting high-fat intake, consuming processed energy-dense foods, or avoiding skipping meals, are well-known to lead to balanced nutrient and energy consumption and improved overall diet quality [ 21 ]. A large meta-analysis [ 29 ] and most longitudinal studies on children [ 30 31 ], though not all [ 32 33 ], consistently reported the benefits of healthy eating behaviors or the consumption of high-quality diets in lowering childhood-obesity risk. Our observations align with the existing sequential axis of “healthy eating behavior,” “high quality of diet,” and “obesity prevention,” [ 34 ] and further corroborates the usefulness of the NQ-P score in early obesity-intervention programs.…”
Section: Discussionmentioning
confidence: 99%